EFFECTIVENESS OF SAP ERP ON SIA QUALITY BASED ON DELONE AND MCLEAN MODELS IN FMCG COMPANIES - Ginting, Anisah Sriulina; Munandar, Agus (Journal of Economic, Bussines and Accounting (COSTING), 2026)
This research investigates the impact of implementing Enterprise Resource Planning (ERP) SAP on performance of Accounting Information Systems (AIS) within a Fast-Moving Consumer Goods (FMCG) organization, framed through the Delone and Mclean Information Systems Success Model. Employing a qualitative descriptive design, the study focuses on a single case. Data were gathered via semi-structured interviews with two primary informants representing the Finance and Accounting division as well as the Supply Chain Management (SCM) department. Analysis was performed using thematic methods, guided by the six dimensions of the Delone and Mclean model: system quality, information quality, service quality, usage, user satisfaction, and net benefits. Results reveal that the adoption of ERP SAP substantially enhances the quality of the AIS. System stability and integration, accurate and relevant information, and responsive IT support contribution to high system usage and user satisfaction. These dimensions collectively result in net benefits, including improved efficiency of accounting processes, data consistency, faster financial reporting, and data-driven decision making. This study confirms that the Delone and Mclean model remains relevant and applicable for evaluating ERP SAP success in the context of FMCG companies in Indonesia.